2016
DOI: 10.1186/s12944-016-0355-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium-enriched bacillus subtilis KT260179 supplementation on chicken growth performance, plasma lipid parameters, tissue chromium levels, cecal bacterial composition and breast meat quality

Abstract: BackgroundBoth chromium (Cr) and probiotic bacillus own the virtues of regulating animal metabolism and meat quality. Purpose of this study was to evaluate the efficiency of supplemental Cr and bacillus in the form of chromium-enriched Bacillus subtilis KT260179 (CEBS) on chicken growth performance, plasma lipid parameters, tissue chromium levels, cecal bacterial composition and breast meat quality.MethodsSix hundred of 1-day-old Chinese Huainan Partridge chickens were divided into four groups randomly: Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
(38 reference statements)
2
24
0
Order By: Relevance
“…The beneficial effects of dietary Bacillus spp. probiotic supplementation on FCR and increased BW of broilers are well documented in many studies (Opalinski et al, 2007;Melegy et al, 2011;Yang et al, 2016;Reis et al, 2017). Spore-forming Bacillus spp.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The beneficial effects of dietary Bacillus spp. probiotic supplementation on FCR and increased BW of broilers are well documented in many studies (Opalinski et al, 2007;Melegy et al, 2011;Yang et al, 2016;Reis et al, 2017). Spore-forming Bacillus spp.…”
Section: Discussionmentioning
confidence: 92%
“…have been known as probiotics for chickens feed because it secretes antimicrobials compounds and suppress the colonization of gut pathogens (Hong et al, 2008;Knap et al, 2011;Guyard-Nicodeme et al, 2016). This probiotic with improve immunity (Melegy et al, 2011) and changes in the intestine morphology of broilers (Sen et al, 2012) lead to promote growth (Melegy et al, 2011) and improves the quality of meat (Xu et al, 2006;Yang et al, 2016). Also, reported that Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…increases in the lightness, redness and yellowness of meat) (Yang et al . ) and eggs (e.g. increases in eggshell thickness, yolk colour, Haugh unit, and decreases in yolk cholesterol) (Xu et al .…”
Section: Mode Of Action and Efficiency Of Bacillus In Terrestrial Andmentioning
confidence: 99%
“…In addition to promoting the growth performance and health of poultry, feed with added Bacillus also improves the quality of meat (e.g. increases in the lightness, redness and yellowness of meat) (Yang et al 2016) and eggs (e.g. increases in eggshell thickness, yolk colour, Haugh unit, and decreases in yolk cholesterol) (Xu et al 2006).…”
Section: Poultrymentioning
confidence: 99%
“…Recent investigations have suggested that the gut microbiota is an important environmental factor affecting energy harvest from the diet and energy storage in mammals, and these studies have focused on the relationship between the gut microbiota and obesity [25][26][27]. Other studies of chickens have shown that the gut microbiota plays a key role in regulating fat metabolism [28,29].…”
Section: Introductionmentioning
confidence: 99%